Buoy-based monitoring of sea surface carbon dioxide partial pressure at Qingdao coastal area - Cao, Lu; Li, Su; Zhang, Shuwei; Wu, Ning; Zhang, Keke; Li, Wenqing; Ma, Ran; Chu, Dongzhi; Wang, Ni; Liu, Yan (Frontiers in Marine Science, 2025)
Continuous time series observations of seawater carbon dioxide partial pressure (pCO2) are crucial for documenting temporal variations in air-sea CO2 fluxes. To examine the seawater pCO2 variation and its influence factors at Qingdao coastal waters, a high-resolution observation of seawater pCO2 near the Xiaomaidao Island was conducted from May 29 to July 25 in 2024. Sea surface pCO2 varied from 519 µatm to 717 µatm during this monitoring period, with an obvious decline and rise from July 12 to 21. The variation of seawater pCO2 was mainly affected by the increasing sea surface temperature, except for the period of pCO2 decrease which was caused by Ulva prolifera bloom. Accompanied by the increase of U. prolifera, sea surface pCO2 decreased to 563 µatm, then the coverage of U. prolifera decreased and sea surface pCO2 rose to 669 µatm during period of July 12 to 21. The observation site acted as a source for atmospheric CO2 throughout the monitoring period, with air-sea CO2 flux ranging from less than 1 mmol m-2 d-1 to over 100 mmol m-2 d-1, resulting in a total CO2 release of 334 mmol m-2. Thus, it is essential for high-resolution measurement of pCO2 in coastal areas.